Phosphorylated Nitrones—Synthesis and Applications - Iwona Rozpara; José Marco-Contelles; Dorota G. Piotrowska; Iwona E. Głowacka (Molecules)
Phosphorylated nitrones belong to an important class of compounds with several applications, such as their therapeutic potency to reduce oxidative stress or as spin-trapping agents. This review covers available synthetic methods for the preparation of both non-cyclic and cyclic phosphorylated nitrones, including the possibilities of the modification of structures with selected functional groups, as well as examples of their application. As reported, the incorporation of diethoxyphosphoryl function into the structure of PBN and DMPO resulted in obtaining their phosphorylated analogs, i.e., N-benzylidene-1-diethoxyphosphoryl-1-methylethylamine N-oxide (PPN) and 5-(diethoxyphosphoryl)-5-methyl-1-pyrroline-N-oxide (DEPMPO), respectively, both forming spin adducts of improved stability in comparison to the reference non-phosphorus nitrones. Moreover, antioxidant and neuroprotective activity observed in the group of phosphorylated nitrones makes them promising candidates for therapeutics.